2014
DOI: 10.1088/2041-8205/783/2/l29
|View full text |Cite
|
Sign up to set email alerts
|

NEAR-IR DIRECT DETECTION OF WATER VAPOR IN TAU BOÖTIS b

Abstract: We use high dynamic range, high-resolution L-band spectroscopy to measure the radial velocity variations of the hot Jupiter in the τ Boötis planetary system. The detection of an exoplanet by the shift in the stellar spectrum alone provides a measure of the planet's minimum mass, with the true mass degenerate with the unknown orbital inclination. Treating the τ Boo system as a high flux ratio double-lined spectroscopic binary permits the direct measurement of the planet's true mass as well as its atmospheric pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
168
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(175 citation statements)
references
References 43 publications
6
168
0
1
Order By: Relevance
“…This is also a rough upper bound for the spectroscopic contrast a spec . Since the cross-correlation analyses described in Section 4.3 are not very sensitive to contrast ratios, varying the value of a spec does not change our conclusions on the RV of the planet, and thus the system inclination (Lockwood et al 2014). However, the specific value of a s does affect our conclusions on the composition and structure of the planet's atmosphere.…”
Section: Model Planetary Spectrummentioning
confidence: 89%
See 2 more Smart Citations
“…This is also a rough upper bound for the spectroscopic contrast a spec . Since the cross-correlation analyses described in Section 4.3 are not very sensitive to contrast ratios, varying the value of a spec does not change our conclusions on the RV of the planet, and thus the system inclination (Lockwood et al 2014). However, the specific value of a s does affect our conclusions on the composition and structure of the planet's atmosphere.…”
Section: Model Planetary Spectrummentioning
confidence: 89%
“…Lockwood et al (2014) showed that the CCF is proportional to the log of the likelihood. At each epoch, we can easily retrieve and confirm the stellar velocity, as shown by the single strong peak in panel A of Figure 5.…”
Section: Two-dimensional Cross-correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to mitigate these issues is by using ground-based highdispersion spectroscopy. For example, detections of sodium and potassium have been presented in the optical (Redfield et al 2008;Snellen et al 2008;Sing et al 2011a;Wood et al 2011;Jensen et al 2011;Zhou & Bayliss 2012;Wyttenbach et al 2015), and detections of carbon monoxide and water in the infrared (Brogi et al 2012(Brogi et al , 2014Rodler et al 2012;de Kok et al 2013;Birkby et al 2013;Lockwood et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Kolbl et al (2015) observed planet-hosting stars from the Kepler survey with optical Keck HIRES spectroscopy in order to search for binary companions with relative radial velocities greater than 10 km s −1 such that the secondary absorption lines are Doppler shifted. A similar technique is used to probe absorption lines in the atmospheres of hot Jupiters, which exhibit rapidly varying velocity offsets (Snellen et al 2010;de Mooij et al 2012;Birkby et al 2013;Lockwood et al 2014). For cases where the hidden companion has a significantly different effective temperature than the target star, Kolbl et al (2015) were also able to detect companions with smaller radial velocity offsets.…”
Section: Introductionmentioning
confidence: 99%